Unintended Changes of Ion-Selective Membranes Composition—Origin and Effect on Analytical Performance - Maksymiuk, Krzysztof (Membranes (Basel), 2020)
Ion-selective membranes, as used in potentiometric sensors, are mixtures of a few important constituents in a carefully balanced proportion. The changes of composition of the ion-selective membrane, both qualitative and quantitative, affect the analytical performance of sensors. Different constructions and materials applied to improve sensors result in specific conditions of membrane formation, in consequence, potentially can result in uncontrolled modification of the membrane composition. Clearly, these effects need to be considered, especially if preparation of miniaturized, potentially disposable internal-solution free sensors is considered. Furthermore, membrane composition changes can occur during the normal operation of sensors—accumulation of species as well as release need to be taken into account, regardless of the construction of sensors used. Issues related to spontaneous changes of membrane composition that can occur during sensor construction, pre-treatment and their operation, seem to be underestimated in the subject literature. The aim of this work is to summarize available data related to potentiometric sensors and highlight the effects that can potentially be important also for other sensors using ion-selective membranes, e.g., optodes or voltammetric sensors.